Zoltán Szvetits (1929-2014): legendary teacher, Zoltán Szvetits passed away - Gaál, István (Teaching Mathematics and Computer Science, 2015)
The legendary mathematics teacher of Secondary School Fazekas in Debrecen, Zoltán Szvetits passed away on 5th November 2014, at the age of 84. Beginning in 1954 he had been teaching here almost forty years. His pupils and the society of teachers have lost an outstanding teacher character. This secondary school has been well known for decades about its special mathematics class with 10 math lessons a week. This special class was designed and established by Zoltán Szvetits.